The beginning - Michelle, Sara ([Costa Mesa, Calif.] : Saddleback Educational Pub., 2012)
Cecilia has always been secure in her world. A high school cheerleader, she is pretty and popular. And she dates Ryan, one of the cutest boys in her school. She leads a charmed and pampered life. Clearly everyone forgot the warnings buried deep in the quatrains of Nostradamus-- the end of days.
Keywords: Teenagers -- Juvenile fiction. End of the world -- Juvenile fiction. Survival --; Juvenile fiction